2013
DOI: 10.1002/cne.23276
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of Pax6 and Pax7 in the adult brain of a urodele amphibian, Pleurodeles waltl

Abstract: Expression patterns of Pax6, Pax7, and, to a lesser extent, Pax3 genes were analyzed by a combination of immunohistochemical techniques in the central nervous system of adult specimens of the urodele amphibian Pleurodeles waltl. Only Pax6 was found in the telencephalon, specifically the olfactory bulbs, striatum, septum, and lateral and central parts of the amygdala. In the diencephalon, Pax6 and Pax7 were distinct in the alar and basal parts, respectively, of prosomere 3. The distribution of Pax6, Pax7, and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
92
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(117 citation statements)
references
References 232 publications
(468 reference statements)
23
92
2
Order By: Relevance
“…Moreover, in the adult brain, it was shown that Pax6 characteristically labeled a population of scattered cells in the striatum, leaving the pallidal region free of labeling [Joven et al, 2013]. The localization of the homologues of the LGE and MGE in amphibians was in agreement with the proposal made on the basis of connectivity and chemoarchitecture in our previous studies [Marín et al, 1998b, c].…”
Section: Amphibianssupporting
confidence: 78%
See 2 more Smart Citations
“…Moreover, in the adult brain, it was shown that Pax6 characteristically labeled a population of scattered cells in the striatum, leaving the pallidal region free of labeling [Joven et al, 2013]. The localization of the homologues of the LGE and MGE in amphibians was in agreement with the proposal made on the basis of connectivity and chemoarchitecture in our previous studies [Marín et al, 1998b, c].…”
Section: Amphibianssupporting
confidence: 78%
“…However, developmental studies in amphibians were still lacking, mainly those that would provide support to the constancy of homologous striatal and pallidal components on the basis of comparable molecular specification (genoarchitectonics) of the counterparts of the LGE and MGE. By means of immunohistochemistry and in situ hybridization, the localization of the territories expressing Dlx, Nkx2.1, Pax6, GAD67 and Isl1, among others, clearly determined the extent of the components of the BG in amphibians [González et al, 2002;Brox et al, 2003;Moreno et al, 2008aMoreno et al, , 2009Joven et al, 2013], readily comparable to their counterparts in amniotes ( fig. 2 ).…”
Section: Amphibiansmentioning
confidence: 99%
See 1 more Smart Citation
“…The mouse anti-Pax6 and anti-Pax7 antibodies developed by Kawakami et al (1997) are the most widely used in anatomical studies, independently of the species studied (Ferran et al, 2008, 2009; Morona et al, 2011; Moreno et al, 2012b; Bandín et al, 2013, 2014; Domínguez et al, 2013, 2014; Joven et al, 2013a,b). In order to develop the antibodies against Pax6 and Pax7, Kawakami et al (1997) first determined the complete nucleotide sequence of the full-length cDNA encoding for Pax6 and Pax7.…”
Section: Methodsmentioning
confidence: 99%
“…Given the difficulty of conducting genetic approaches to the study of the neuroanatomy of so many species, we will rely on immunohistochemical techniques that use antibodies against the transcription factors, which are largely conserved. The validity of this approach has been reinforced by the localization of these transcription factors that, in addition to being expressed during development, are also found in adult animals; their distribution serves as a tool for recognizing brain regionalization, particularly those many entities that are not cytoarchitectonically distinct (González and Northcutt, 2009; Moreno et al, 2010, 2012b; Ferreiro-Galve et al, 2012; Bandín et al, 2013; Joven et al, 2013a,b). The results of this comparative analysis highlight that the expressions of Pax6 and Pax7 are highly conserved within the whole group of sarcopterygians (lungfishes and tetrapods) suggesting a similar role of these genes in the regionalization of the brain and the specification of corresponding cell populations.…”
Section: Introductionmentioning
confidence: 99%